HUMAN MOTIVITY AS REFERENCE FOR HEALTH AND QUALITY OF LIFE (Fiep Bulletin - online, 2011)
Nowadays, studies regarding health and quality of life represent great relevance for both people within the health field and general population. The present article's objective is to approach questions regarding health and quality of life from the human motivity paradigm. It helps physical education to better comprehend the human wholeness thus promote practices committed to the general population health. The method employed was a bibliographical research on university libraries and websites such as SCIELO and Google Scholar from the human motivity, health and quality of life terms. This research shows the human motivity importance in health-related matters, and how it adds value to the human condition wholeness.
Keywords: human motivity; heath; quality of life